CROWN STRUCTURE MODIFICATIONS IN RELATION TO AIR-POLLUTION (LANDSCAPE AND URBAN PLANNING, 1993)
Analysis of crown structure and crown modifications plays a role of primary importance in surveys of `new types of forest damage', since it is a decisive parameter in assessing the health status of a tree. Several forms of ramification alterations have been described in central and northern European species (Norway spruce, beech, Durmast oak, English oak, birch). This study examines the situation in Tuscany and offers a description of the alterations found in the main species typical of the Mediterranean region (Turkey oak, pubescent oak, holm oak, stone pine). The article discusses the potential impact of these alterations on the most typical forest formations, the ones which characterize the Tuscan landscape, and it describes the modifications already under way.